An Energy Efficient Receiver-based Flooding Scheme Using 1-Hop Neighbours Geographical Information for MANETs - Pham, Duy Ngoc; Mi Nguyen, Dac Quynh; Choo, Hyunseung (Journal of Telecommunications and the Digital Economy, 2018)
Flooding is a fundamental, critical, and indispensable operation to support various applications and protocols in wireless ad hoc networks. The traditional flooding scheme generates excessive redundant packet retransmissions, causing contention and packet collisions, and ultimately wasting limited bandwidth and energy. Some recent flooding schemes that avoid those problems have been studied. They can achieve local optimality and have lower computational complexity. However, drawbacks limit the efficiency of these schemes. In this paper, we propose an efficient flooding protocol that minimizes flooding traffic, leveraging location information of 1-hop neighbor nodes. Our scheme is receiver-based; it does not piggyback any neighbor information. We prove theoretically that the proposed scheme achieves 100 percent deliverability. Simulation shows our scheme to be highly efficient. It consumes less energy, reduces the number of forwarding nodes almost to that of the benchmark, but maintains a high delivery ratio.